PROPOLIS EXTRACT SORPTION AS A PULPCAPPING AGENT - Isyana Erlita; Rahmatillah Rahmatillah; Sherli Diana (FKG Unlam, 2021)
ABSTRACTBackground: This research is an experimental study to determine the physical properties of propolis extract as an alternative material in pulpcapping treatment. High sorption value is the main cause of pulpcapping treatment failure. Purpose: to analyze the sorption value of propolis extract in water and artificial saliva. Materials and Methods: Thirty disc-shaped zinc oxide propolis (15 mm x 1 mm) specimens were stored in the incubator at 37ºC for 24 hours. The discs were weighed, dehydrated, and weighed again. Immediately after weighing, the discs were immersed for 1 day, 3 days, and 7 days in 50 mL of distilled water and artificial saliva at 37ºC and then weighed for second time (sorption value). Data were analyzed by one way ANOVA for data processing in the water and artificial saliva immersion group, then the Independent T-Test for inter-group immersion in water with artificial saliva. Results: There were differences in the sorption value of zinc oxide propolis with ZnOE (positive control) in water and artificial saliva between immersion times of 1 day, 3 days, and 7 days. There was no difference in the sorption value of zinc oxide propolis between the water and the artificial saliva immersion group. Conclusion: The sorption value of propolis extract, both in water and artificial saliva immersion shows a high sorption value. This indicates that the propolis extract has not met the criteria as a pulpcapping material in terms of its physical properties, namely absorption of water (water sorption).Keywords: Propolis extract, Pulpcapping, Sorption